2016
DOI: 10.1158/1535-7163.mct-15-0500
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mps1 Kinase Inhibitors with Potent Antitumor Activity

Abstract: Monopolar spindle 1 (Mps1) has been shown to function as the key kinase that activates the spindle assembly checkpoint (SAC) to secure proper distribution of chromosomes to daughter cells. Here, we report the structure and functional characterization of two novel selective Mps1 inhibitors, BAY 1161909 and BAY 1217389, derived from structurally distinct chemical classes. BAY 1161909 and BAY 1217389 inhibited Mps1 kinase activity with IC 50 values below 10 nmol/L while showing an excellent selectivity profile. I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
109
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(113 citation statements)
references
References 34 publications
(26 reference statements)
4
109
0
Order By: Relevance
“…: 2014-002023-10) are currently in phase I clinical trials. As has been presented for CFI-402257, these inhibitors have cellular on-target activity and have significant tumor growth-inhibitory activity in preclinical models (27,28). However, comparison of the reported pharmacological properties and preclinical data for these inhibitors reveals differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…: 2014-002023-10) are currently in phase I clinical trials. As has been presented for CFI-402257, these inhibitors have cellular on-target activity and have significant tumor growth-inhibitory activity in preclinical models (27,28). However, comparison of the reported pharmacological properties and preclinical data for these inhibitors reveals differences.…”
Section: Discussionmentioning
confidence: 99%
“…Mps1 inhibitors are mitosis-promoting agents that, when used with antitubulin agents, which perturb proper chromosome alignment, are expected to increase chromosome segregation errors above the threshold required to kill cancer cells. In support of this hypothesis, Mps1 inhibitors have been shown to sensitize cancer cells to taxane treatment (29), and this approach is being tested clinically (27). Furthermore, the combination of Mps1 and cyclin-dependent kinase 4/6 inhibition has been investigated as a strategy to increase the therapeutic window for Mps1 inhibitors (30).…”
Section: Discussionmentioning
confidence: 99%
“…Several Mps1/TTK inhibitors have been developed in recent years. 66,73 In 2017, novel small molecule Mps1/TTK inhibitors have been identified as potential targeted therapies for breast cancers, (Compound 17) inhibits in vitro kinase activity of Mps1 with an IC50 value of 0.809 µM and (Compound 18) which is the most promising in the study with an IC50 value of 0.356µM. 74 Future indepth investigations of both anticancer activities and safety profiles of these Mps1 inhibitors are warranted.…”
Section: Compound 13mentioning
confidence: 99%
“…Mps1 is a dual specificity kinase that can phosphorylate serines/threonines and tyrosines. Mps1 function as the key kinase that activates the spindle assembly checkpoint (SAC) [3] . Along with other cellular processes, MPS1 kinases also function in multiple roles in mitosis, including spindle pole duplication [4] , mitotic checkpoint signaling, mitotic cytokinesis and the maintenance of CIN [5,6] .…”
Section: Introductionmentioning
confidence: 99%
“…Several compounds that have Mps1 inhibitory activity have been identified and their anticancer activity has been studied [13,14] . BAY1161909 and BAY1217389 are the two highly selective Mps1 inhibitor that are in phase 1 clicnical trials [3] . Our research group has reported several review and research articles on insilico techniques such molecular docking and 3D-QSAR studies [15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%